Environmental variables measured across peatland drainage gradients in Minnesota, USA - Defrenne, Camille; Tucker, Colin L; Lilleskov, Erik A (PANGAEA, 2023)
Data were collected to investigate the effect of a century-long drainage on soil fungal communities. We selected three acidic, nutrient-poor peatlands in Minnesota adjacent to ditches dug between 1916 and 1918 and separated by 5–15 km (CH-Church Road; NW- Northwoods, and AR-Arkola). In each peatland, we established a single transect (c. 215–525 m long) from interior (undrained) to ditch (drained). From September 13 to September 15 2021, we collected ten peat blocks (20x20x40 cm) along each transect at ca. 20–45-m intervals with similar microtopography (i.e. lawns) using a serrated knife. Upon collection, cores were cut in half lengthwise and sectioned into 10-cm-depth increments (0–10, 10–20, 20–30, and 30–40 cm). From each section, a representative subsample (ca. 5 g) was collected by hand using sterile gloves, wrapped in plastic and foil, stored in liquid nitrogen for 1–3 day(s) and stored at -80°C for c. 1 month until processing. The remaining peat from each section was analyzed for total carbon and nitrogen (Costech 4010 Elemental Combustion System, Costech Analytical Technologies Inc., Valencia, CA, USA), and for the degree of decomposition using the von Post scale of humification. Peat for the focal dataset presented here was processed from the 10 to 20-cm and 20 to 30-cm-depth increments. In addition, we surveyed vegetation (shrub ground cover, % and tree basal area, m2 ha-1), measured water table depth (cm), change in peat height (m) and collected peat samples for bulk density (g cm-3), and plant fine-root density (indicator of belowground resource allocation; g cm-3) at each sampling location along the transects.
Keywords: drainage; ectomycorrhizal fungi; Peatland; Subsidence; vegetation gradient; vegetation survey